2021
DOI: 10.1111/joim.13352
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension genetics past, present and future applications

Abstract: sion genetics past, present and future applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 128 publications
(198 reference statements)
0
32
0
3
Order By: Relevance
“…However, the use of endothelin receptor antagonists has not been shown to be beneficial in the heart failure population, with some studies demonstrating worse outcomes when used in patients with left heart failure [ 39 , 40 ]. Studies are ongoing evaluating other components of the endothelin signaling pathway as potential novel therapies in cardiovascular disease [ 41 , 42 ]. Recently, Leary and colleagues revealed that elevated ET-1 levels may be associated with a more favorable cardiovascular outcome, suggesting that the role of ET-1 is still not well defined [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of endothelin receptor antagonists has not been shown to be beneficial in the heart failure population, with some studies demonstrating worse outcomes when used in patients with left heart failure [ 39 , 40 ]. Studies are ongoing evaluating other components of the endothelin signaling pathway as potential novel therapies in cardiovascular disease [ 41 , 42 ]. Recently, Leary and colleagues revealed that elevated ET-1 levels may be associated with a more favorable cardiovascular outcome, suggesting that the role of ET-1 is still not well defined [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Large genome-wide association studies (GWAS) have identified >2,000 genetic variants associated with different BP components , reflecting the high heritability of BP. [21][22][23][24][25][26][27] However, most of the previous GWAS have been largely restricted to individuals of European ancestry, with limited data from Chinese and other East Asian ancestry populations, in which the genetic architecture, environmental All rights reserved. No reuse allowed without permission.…”
Section: Introductionmentioning
confidence: 99%
“…Large genome-wide association studies (GWAS) have identified >2,000 genetic variants associated with different BP components , reflecting the high heritability of BP. [21][22][23][24][25][26][27] However, most of the previous GWAS have been largely restricted to individuals of European ancestry, with limited data from Chinese and other East Asian ancestry populations, in which the genetic architecture, environmental exposures, and healthcare provision for treatment of high BP may differ substantially from those in Western populations. Moreover, most of the previous genetic studies have focused on SBP and DBP and, hence, relatively little is known about the genetic determinants of other BP traits including PP and MAP and their causal relevance for CVD.…”
Section: Introductionmentioning
confidence: 99%
“…Even so, conflicting results have been obtained, particularly among African population studies (Al-Kordy et al, 2012;Nassereddine et al, 2015;Amrani-Midoun et al, 2016;Ghogomu et al, 2016). Thus, several authors have emphasized the need to conduct more African studies to further validate the role of MTHFR polymorphisms in the pathogenesis of HTN (Amrani-Midoun et al, 2016;Ghogomu et al, 2016;Olczak et al, 2021).…”
Section: Introductionmentioning
confidence: 99%